Sericin-Assisted Green Synthesis of Gold Nanoparticles as Broad-Spectrum Antimicrobial and Biofilm-Disrupting Agents for Therapy of Bacterial Infection - Cai R; Cheng Q; Zhao J; Zhou P; Wu Z; Ma X; Hu Y; Wang H; Lan X; Zhou J; Tao G (International Journal of Nanomedicine)
Rui Cai,1,2,* Qian Cheng,1,3,* Jiayu Zhao,1 Peirong Zhou,1 Zhaodan Wu,1 Xuemin Ma,1 Yajuan Hu,1 Huiyue Wang,1 Xiaorong Lan,1,2 Jing Zhou,1,4 Gang Tao1,2 1Luzhou Key Laboratory of Oral & Maxillofacial Reconstruction and Regeneration, The Affiliated Stomatological Hospital, Southwest Medical University, Luzhou, 646000, People’s Republic of China; 2Institute of Stomatology, Southwest Medical University, Luzhou, 646000, People’s Republic of China; 3Department of Orthodontics, The Affiliated Stomatological Hospital, Southwest Medical University, Luzhou, 646000, People’s Republic of China; 4Department of Oral and Maxillofacial Surgery, The Affiliated Stomatological Hospital, Southwest Medical University, Luzhou, 646000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Zhou, Department of Oral and Maxillofacial Surgery, The Affiliated Stomatological Hospital, Southwest Medical University, Luzhou, 646000, People’s Republic of China, Email 770384391@qq.com Gang Tao, Luzhou Key Laboratory of Oral & Maxillofacial Reconstruction and Regeneration, The Affiliated Stomatological Hospital, Southwest Medical University, Luzhou, 646000, People’s Republic of China, Email taogang@swmu.edu.cnBackground: Tens of millions of people die from wound infections globally each year, and nearly 80% of tissue infections are associated with bacterial biofilms. However, overuse of antibiotics can lead to bacterial resistance. Therefore, it is critical to develop simple and effective strategies to kill bacteria and remove biofilms.Methods: The present study used sericin as a reducing and stabilizing agent to synthesize sericin-gold nanoparticles (Ser-Au NPs) and tested its colloidal stability under different pH and salt concentration conditions. Subsequently, functional gold nanocomposites (Ser-Au@MMI) were synthesized by combining Ser-Au NPs with 2-mercapto-1-methylimidazole (MMI). The antimicrobial effect of Ser-Au@MMI was checked by MIC, antimicrobial activity test, and in vitro cytotoxicity was assessed using CCK-8 assay. In vitro anti-biofilm effect was observed by fluorescence microscopy and SEM. Finally, the anti-infective therapeutic efficacy of Ser-Au@MMI was determined in an in vivo rat-infected wound model.Results: Sericin as a reducing and stabilizing agent to synthesize Ser-Au NPs exhibited excellent colloidal stability under different pH and salt concentration conditions. The TEM, EDS, and XPS analyses confirmed the successful synthesis of Ser-Au@MMI. It exhibited higher antibacterial activity due to the synergistic effect of MMI and AuNP, which can achieve a bactericidal effect by destroying the integrity of bacterial cell walls and structure. In addition, Ser-Au@MMI10 (HAuCl4:MMI =1:10) concentration (64 μg/mL) could effectively disrupt biofilms formed by four species of bacteria and kill them, including P. aeruginosa, B. subtilis, E. coli, and S. aureus, but was not cytotoxic to mouse fibroblasts (L929) cells. Infected wound modeling showed that Ser-Au@MMI10 accelerated infected wound healing in vivo.Conclusion: Ser-Au@MMI nanocomposites are prepared through a facile and environmentally friendly strategy and have the advantages of excellent bactericidal effect and low toxicity, which has the potential for application as a broad-spectrum antimicrobial agent and biofilm disrupting agent in healthcare.Keywords: antibacterial, gold nanoparticles, green synthesis, wound healing, sericin